Youngest Adults Less Likely to Read News Online. (September 2014) - Kaufhold, Kelly
An analysis of Pew Center survey data from 2002 to 2010 finds young adults continue to lag behind other adults in reading news, even when it is online. While nine of 10 young adults are likely to be online, the oldest Americans (65+) are more likely to follow news online.